Manajemen Program Pemberian Makan Sayur untuk Mencegah Picky Eaters pada Anak Usia Dini - Uci Suryaningsih (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
The problem of picky eaters in early childhood is a challenge that can have an impact on optimal growth and development of children. Children who only like certain types of food have the potential to be deficient in essential nutrients. This study aims to describe the management of the vegetable eating habit program at Diponegoro Kindergarten 118 Bentul Kebasen as an effort to prevent picky eater behavior. This study uses a descriptive qualitative method with data collection techniques through in-depth interviews. The results of the collection show that the implementation of the vegetable eating habituation program has been going on for five years with full support from schools, teachers and parents of students. This program is carried out every day by involving students to get used to consuming vegetables